Government finance under alternative monetary arrangements: the OECS and Barbados - Anyadike-Danes, M.K. (ISER MonaJA, 1993)
Analyses governments revenue collection in the Eastern Caribbean in the 1980's. Examines changes in the ratio of taxes to GDP, comparing first the OECS; (as an aggregate) to Barbados, and then the member countries of the OECS to each other. Explores changes in the composition of tax collections, again making comparisons between the OECS and Barbados, and then between OECS States.